Bilateral functional ptosis in adolescence: a case report - Sofia Vaz Pinto; Ana I. Gonçalves; Inês de Oliveira; Andreia Pereira (Publicaciones Permanyer, 2024)
Introduction: Bilateral eyelid ptosis is an extremely rare form of functional neurological disorder (FND). FNDs are a group of disorders that have in common the absence of a structural pathology of the nervous system and the presence of common neurological symptoms, and can be somewhat challenging in regard to diagnosis, approach, and treatment. Case report: We present the case of an adolescent diagnosed with sudden asymmetric ptosis. To consider the different potential diagnoses (cranial polyneuropathy, mitochondrial disease, and neuromuscular junction disorder), the patient underwent several complementary diagnostic tests, which gave inconclusive results. Although there had been no recent stressful events, the observed inconsistency and incongruity, as well as the observation of certain details in the neurological exam, led to a diagnosis of FND. Six days after clinical discharge, the patient recovered suddenly and spontaneously from all neurological problems. Discussion: Relevant symptoms and an accurate assessment of psychological factors are fundamental to ensuring a correct diagnosis and positive prognosis.